The effect of Total Asset Turn Over (TATO) and Current Ratio (CR) on Return On Asset (ROA) at PT Unilever Indonesia Tbk. - Sulafifah Putri Arrohman; Achmad Agus Yasin Fadli (Indonesian Development of Economics and Administration Journal, 2022)
This study aims to determine the simultaneous and partial influence of the independent variable, namely Total Asset Turn Over (TATO) and Current Ratio (CR) on the dependent variable, namely Return On Asset (ROA). This research was conducted at PT Unilever Indonesia Tbk. The type of research used in this study was associative research. The population used in this study is the company's financial statement data in the form of balance sheet and profit and loss financial statements, and the number of samples used is the balance sheet and profit and loss financial statements for 10 years, namely 2013 to 2022. The data collection method in this study was carried out by literature or secondary studies. The data analysis techniques used are multiple regression, classical assumption test, t test, f test, and coefficient of determination. Based on the results of the study, it can be concluded that simultaneously Total Asset Turn Over (TATO) and Current Ratio (CR) have a significant effect on Return On Asset (ROA) at PT Unilever Indonesia Tbk, partially Total Asset Turn Over does not have a significant effect on Return On Asset and partially Current Ratio has a significant effect on Return On Asset at PT Unilever Indonesia Tbk for the 2013-2022 period.